The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1745-6215-15-438
|View full text |Cite
|
Sign up to set email alerts
|

Blocking and reversing hepatic fibrosis in patients with chronic hepatitis B treated by traditional Chinese medicine (tablets of biejia ruangan or RGT): study protocol for a randomized controlled trial

Abstract: BackgroundChronic hepatitis B (CHB) can progress to cirrhosis, hepatocellular carcinoma (HCC) and ultimately liver-related death. Although oral antiviral therapy for patients with CHB reduces the risk of such complications, once cirrhosis is established, the benefits of antiviral therapy are not robustly demonstrated. According to traditional Chinese medicine (TCM), some Chinese herbal medicines promote blood circulation and soften hard masses, and therefore they may block and reverse hepatic fibrosis. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A number of clinical trials have been performed to assess the therapeutic efficacy and safety of CHM products. 1 13 14 On the other hand, a recent cohort study reported that adjunctive therapy with CHM may improve the survival of patients with liver cancer. 15 Although nucleoside analogue therapy is associated with reduced risk of HCC in patients with CHB virus infection and experience fewer side effects, in many cases the drug resistance and viral variation limit their efficacy as therapeutic agents for CHB.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical trials have been performed to assess the therapeutic efficacy and safety of CHM products. 1 13 14 On the other hand, a recent cohort study reported that adjunctive therapy with CHM may improve the survival of patients with liver cancer. 15 Although nucleoside analogue therapy is associated with reduced risk of HCC in patients with CHB virus infection and experience fewer side effects, in many cases the drug resistance and viral variation limit their efficacy as therapeutic agents for CHB.…”
Section: Introductionmentioning
confidence: 99%
“…This was a multicenter prospective sub-study of our ongoing clinical trial of regression of HBV-related liver fibrosis in China (NCT01965418)[25]. The study meets the requirements of the Declaration of Helsinki, the protocol was approved by the ethics committee of each participating institution, and written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine has been selected as an alternative treatment for liver fibrosis because of the low efficiency and unexpected side effects of the currently used therapeutic strategy [5]. Numerous herbal medicines are used for liver fibrosis therapy in clinical practice [6][7][8]. The Fuzheng Huayu formula is one of the most well-studied antifibrotic agents and has a good therapeutic effect on hepatitis B-induced cirrhosis [9,10].…”
Section: Introductionmentioning
confidence: 99%